Pengaruh Model Siklus Belajar 7E Terhadap Kemampuan Pemecahan Masalah Matematika Ditinjau dari Pengetahuan Awal Siswa - I Gusti Agung Handayani (FPMIPA IKIP PGRI Bali, 2018)
Research is done in SMA Negeri 1 Abiansemal, with the population of all science class X students in learning year of 2017/2018 is as much as 252 students. The type of this research is quasi experiment, with the research factorial 2x2. The taking of sample is done by simple random sampling technique. The data of student’s pre- knowledge, and the student’s ability in solving mathematic problem are collected continously through pre-knowledge test and ability test in solving the problem in the form of essay test. The data of pre/initial competence and the ability of students in solving the mathematic problem is analyzed by using descriptive statistic and ANAVA test. Based on analysis result, is found the results as following : (1) the student’s ability in solving mathematic problem by studying with learning cycle “7E” model is better than conventional learning seeing from high pre-knowlege; (2) the student’s ability by studying with conventional learning is better than learning cycle “7E” model seeing from low pre-knowlege; (3) there is an interaction learning models (learning cycle “7E” and conventional) and student’s pre-knowledge (hing and low) toward the student’s ability in solving the mathematic problem.